On criminal governance, resilience and comprehensive security strategies - García Gallegos, Bertha (2024)
It is about thinking, from a social sciences perspective, about the content and differences between the forms of violence that arise in contexts where criminal economies are prevalent, as well as the pre-social primordial condition of violence. Its control through cultural processes has depended and continues to depend on the possibilities of building agreements and consensus. This article explores the use of the concepts of Governance and Resilience through recent studies on criminal networks. It contrasts the historical experience of violence control, which was predominantly based on military force until the late 20th century, with the more recent developments in constructivist and systemic theories of Security with a social focus. These developments have led to methodologies for building Resilience based on strengthening institutions and social fabric, as proposed by the “Global Initiative against organized crime”.